Formative movement of teachers from the early years about fraction: the whole (Research, Society and Development, 2020)
This article is the result of a master's research that analyzed the training movement of teachers in the early years, about different meanings of fractions and their relationship with teaching in teacher training. A space for teacher training in the early years of elementary school in public schools was promoted from an extension course, to investigate, discuss and explore knowledge about the concept of fractions and their different pedagogical meanings and practices, and where they were produced the data, through filming, images, audiovisual recordings, written and recorded reports, discussion forum, narratives and initial and final questionnaires giving this research a qualitative characteristic. The objective of this article is to investigate the formative process when treating the idea of ​​fraction as part-whole in the collective starting from the part and, identifying scenes that indicated appropriations of this concept of these student teachers. The study is based on the assumptions of Historical-Cultural Theory and approaches Dialectical Historical Materialism as a research method and the historical logical movement of the concept as the basis for the teacher's learning and teaching work. We investigated the formation movement of that collective about the composition of the whole from the part, we identified scenes that proved that there was appropriation or expansion of knowledge about the different possibilities of composition of this whole known by the part. We conclude that the part-whole fraction, even though it is one of the ideas mentioned in studies as the most practiced and known by teachers, needs to be approached in different ways and needs to be discussed in continuing education.